Treatment of Multi-Drug-Resistant Tuberculosis with Second- Line All-Oral Drugs in Ghana: Incidence of Adverse Events - Bukari, E. T. (University of Ghana, 2024)
Introduction: The treatment of multidrug-resistant tuberculosis (MDR-TB) remains challenging due to the toxicity of second-line medications and suboptimal treatment outcomes. This study aimed to determine the incidence of adverse events and identify factors associated with these events in patients undergoing treatment for MDR-TB with second-line all-oral drugs in Ghana. Methods: This retrospective cohort study reviewed the medical records of 384 MDR-TB patients treated with second-line all-oral drugs at selected health facilities in Ghana, including the Greater Accra Regional Hospital, Eastern Regional Hospital, and Kumasi South Hospital. Data were extracted using the Kobo Collect tool, capturing patient demographics, baseline clinical and laboratory characteristics, treatment regimens, and adverse events. The study period spanned from 2020 to August 2024. Results: The mean age of patients was 45 years (SD = 15), with the majority being male (65.78%). Most patients were aged 45–64 years (33.85%), and HIV was the most common comorbidity (19.5%). The most frequent adverse events were diarrhea (14%), dizziness (13.7%), and vomiting (12.3%), mostly mild to moderate in severity. Severe adverse events such as leukopenia and acute kidney injury were rare (<5%). Over time, gastrointestinal symptoms such as vomiting and nausea decreased significantly. Multivariate analysis revealed that patients with comorbidities such as diabetes or hypertension were significantly more likely to experience adverse events (aRR = 2.65, 95% CI: 1.58–4.43, p < 0.001). In contrast, patients aged 65 years and above had a notably lower risk of developing adverse events (aRR = 0.44, 95% CI: 0.25–0.79, p = 0.005). Sex was not significantly associated with adverse events (aRR = 1.03, p = 0.86). Overall, 74.9% of patients achieved successful treatment outcomes, while 25.1% experienced treatment failure, relapse, or death. Conclusion: In conclusion, adverse events are common in the treatment of MDR-TB with second line All-Oral drugs, with gastrointestinal adverse events being the most prevalent. These findings highlight the importance of monitoring and managing adverse events to optimize treatment outcomes for MDR-TB patients in Ghana
MSc. Clinical Trials
Keywords: multidrug-resistant tuberculosis (MDR-TB); Ghana; toxicity